Screening programme evaluation applied to airport security. Issue 7633 (20th December 2007) - Linos, Eleni; Linos, Elizabeth; Colditz, Graham
Abstract : Eleni Linos, Elizabeth Linos, and Graham Colditz investigate whether airport security screening would pass the National Screening Committee's criteria for an effective screening test